Saturated, Suffocated, and Salty: Human Legacies Produce Hot Spots of Nitrogen in Riparian Zones. Issue 12 (9th December 2022) - Inamdar, Shreeram P.; Peck, Erin K.; Peipoch, Marc; Gold, Arthur J.; Sherman, Melissa; Hripto, Johanna; Groffman, Peter M.; Trammell, Tara L. E.; Merritts, Dorothy J.; Addy, Kelly; Lewis, Evan; Walter, Robert C.; et al.
Abstract: The compounding effects of anthropogenic legacies for environmental pollution are significant, but not well understood. Here, we show that centennial‐scale legacies of milldams and decadal‐scale legacies of road salt salinization interact in unexpected ways to produce hot spots of nitrogen (N) in riparian zones. Riparian groundwater and stream water concentrations upstream of two mid‐Atlantic (Pennsylvania and Delaware) milldams, 2.4 and 4 m tall, were sampled over a 2 year period. Clay and silt‐rich legacy sediments with low hydraulic conductivity, stagnant and poorly mixed hydrologic conditions, and persistent hypoxia in riparian sediments upstream of milldams produced a unique biogeochemical gradient with nitrate removal via denitrification at the upland riparian edge and ammonium‐N accumulation in near‐stream sediments and groundwaters. Riparian groundwater ammonium‐N concentrations upstream of the milldams ranged from 0.006 to 30.6 mgN L −1 while soil‐bound values were 0.11–456 mg kg −1 . We attribute the elevated ammonium concentrations to ammonification with suppression of nitrification and/or dissimilatory nitrate reduction to ammonium (DNRA). Sodium inputs to riparian groundwater (25–1, 504 mg L −1 ) from road salts may further enhance DNRA and ammonium production and displace sorbed soil ammonium‐N into groundwaters. This study suggests that legacies of milldams and road salts may undercut the N buffering capacity of riparian zones and need to be considered in riparian buffer assessments, watershed management plans, and dam removal decisions. Given the widespread existence of dams and other barriers and the ubiquitous use of road salt, the potential for this synergistic N pollution is significant. Plain Language Summary: Human activities can combine to exacerbate environmental pollution. We studied the effects of milldams and road salt runoff on nitrogen (N) pollution in streamside/riparian soil and groundwaters in Pennsylvania (Chiques Creek) and Delaware (Christina River). While nitrate‐N concentrations in groundwaters and soils were low, ammonium‐N concentrations for both sites were unexpectedly high. We attributed the high groundwater ammonium concentrations to processes of ammonification and/or dissimilatory nitrate reduction to ammonium that occurred under stagnant and persistently reducing riparian groundwater conditions. Road salt runoff inputs from an interstate highway above the Christina River site likely exacerbated the groundwater ammonium concentrations because of sodium displacement of ammonium‐N from sediment surfaces into solution. We suggest that dam removals could enhance the natural variability in groundwater, induce nitrification‐denitrification removal of N, and thus mitigate N pollution in riparian zones. Greater consideration needs to be given to environmental impacts of human legacies in watershed management. Key Points: The coupled effects of anthropogenic legacies for nitrogen dynamics are not well understood Ammonium‐N may accumulate in riparian groundwater and sediments upstream of milldams due to stagnant, poorly mixed, and reducing conditions Road salt salinization may further enhance the concentrations of ammonium in riparian groundwaters